2012
DOI: 10.1152/japplphysiol.01215.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of V̇o2 kinetics by O2 delivery: insights from acute hypoxia and heavy-intensity priming exercise in young men

Abstract: Spencer MD, Murias JM, Grey TM, Paterson DH. Regulation of VO 2 kinetics by O2 delivery: insights from acute hypoxia and heavy-intensity priming exercise in young men. J Appl Physiol 112: 1023-1032, 2012. First published December 22, 2011 doi:10.1152/japplphysiol.01215.2011.-This study examined the separate and combined effects of acute hypoxia (Hypo) and heavy-intensity "priming" exercise (Hvy) on pulmonary O 2 uptake (V O2p) kinetics during moderate-intensity exercise (Mod). Breath-by-breath V O2p and near-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 37 publications
5
34
1
Order By: Relevance
“…The data presented in this study are part of a larger project also looking at the effects of hypoxia on V O2 kinetics. As such, parts of the data regarding the effects of priming exercise on the V O2 and [HHb] kinetics response from 9 of the 12 subjects were previously presented as the control data relative to an hypoxia intervention (22), whereas the present paper adds the focus on the Q cap kinetics. All procedures were approved by The University of Western Ontario Research Ethics Board for Health Sciences Research Involving Human Subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in this study are part of a larger project also looking at the effects of hypoxia on V O2 kinetics. As such, parts of the data regarding the effects of priming exercise on the V O2 and [HHb] kinetics response from 9 of the 12 subjects were previously presented as the control data relative to an hypoxia intervention (22), whereas the present paper adds the focus on the Q cap kinetics. All procedures were approved by The University of Western Ontario Research Ethics Board for Health Sciences Research Involving Human Subjects.…”
Section: Methodsmentioning
confidence: 99%
“…These studies collectively showed that, although intracellular mechanisms are likely the principal putative factors controlling the adjustment of V O 2 kinetics during the initial response to a step increment in power output, for pulmonary V O 2p time constant (V O 2p ) values greater than ϳ20 s, the rate of adjustment of phase II V O 2p is also constrained by the matching of local O 2 delivery to muscle V O 2 . More specifically, we have shown recently that a significant reduction in the phase II V O 2p when moderate-intensity exercise is preceded by a bout of heavy-intensity (i.e., supra-lactate threshold) "priming" exercise was related to improvements in the matching of O 2 delivery to O 2 utilization, as reflected by reductions in the [HHb]/V O 2 ratio (16,22). Using a somewhat similar approach, Buchheit et al (4) indicated that a smaller V O 2p during the second bout of moderate-intensity running in those participants in whom the first bout showed a rather slow rate of adjustment for phase II V O 2p was related to improvements in O 2 provision, as reflected by a faster adjustment of Q cap [i.e., Q cap mean response time (MRT)].…”
mentioning
confidence: 99%
“…Most commonly, the literature will refer to either the anaerobic threshold, lactate threshold, metabolic threshold, gas exchange threshold, or ventilation threshold (VT) when designing steady state exercise protocols (Hughson & Morrisey, 1982;Rossiter et al, 1999;Koppo et al, 2004;Murias et al, 2010;Spencer et al, 2012;McNulty et al, 2015). Surpassing of the lactate threshold is 14…”
Section: What Is Steady State?mentioning
confidence: 99%
“…Nevertheless, some researchers quantify the time difference between the onset of exercise and the end of phase-I (i.e. the phase-I duration) as a time delay Barstow & Mole, 1991;Grassi et al, 1996;Spencer et al, 2012). See Figure 2-4 for a graphical representation of all three phases.…”
Section: The Phases Of the V̇o 2 Kinetic Response To Steady Statementioning
confidence: 99%
See 1 more Smart Citation